For Track buffs: Additional Analyses and Statistics behind "Track & Battlefield" - Sailer, S.; Seiler, S.
The "Track & Battlefield" article is based on a sizable study of trends in world-class running. (1) The article's section on ethnic bell curves in men's track is based on data from Peter Larrson's superb website. My 400k Excel 5.0 workbook containing the data on ethnic differences in track performance by event (as of 10/19/97) can be downloaded here. It contains lots of interesting data on other ethnic groups' bell curves, like East Asians, Ethiopians, and Mexicans. I hope all the runners' ethnic attributions are correct, but I'd appreciate suggestions (e.g., I put the great Cuban 400m-800m man, Alberto Juantorena, as being of European descent; if you think he's more West African than European, please let me know). One interesting point is that there are surprisingly few of these ambiguous cases.